Implementation of international standards to the legislation of the Republic of Kazakhstan: Definition and mechanisms - Oralova, Y.; Rakisheva, A. (Life Sci J Vol 11 No 11s, 341-347, 2014)
The article is devoted to the consideration of mechanisms and forms of implementation of the international standards in the field of space activities and education sphere to the legislation of the Republic of Kazakhstan. For this purpose, the article provides a comparative analysis of the provisions of international standards and the legislation of the Republic of Kazakhstan. Purpose–the authors have tried to define the mechanisms of implementation of international standards applied by the Republic of Kazakhstan. Methodology–theoretical methods, induction and deduction, method of comparative analysis, legalistic method. Value–authors have tried to give the definition of the term “implementation”in doctrine of international law and the analysis of the most widespread ways of implementing of international standards to domestic law in different spheres of public relations. Results–the most widespread implementation mechanisms in the legislation of the Republic of Kazakhstan are incorporation and transformation. Sometimes specification and reference are also used.
Keywords: implementation, international standards, obligations, domestic law, space activities, education sphere